2019
DOI: 10.1016/j.euf.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Preoperative Severe Renal Insufficiency on Poor Postsurgical Oncological Prognosis in Patients with Urothelial Carcinoma

Abstract: In this report, we found that preoperative severe renal insufficiency (estimated glomerular filtration rate<45ml/min/1.73m) had higher risk for relapse and lower survival probability. Close attention is necessary when urothelial carcinoma patients have severe renal insufficiency before radical cystectomy or nephroureterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 30 publications
3
33
0
Order By: Relevance
“…The follow‐up protocol in the Taiwan and Japan cohorts is as disclosed in previous studies . The end‐point of this study was to observe the natural course of UTUC within 5 years between these two groups.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The follow‐up protocol in the Taiwan and Japan cohorts is as disclosed in previous studies . The end‐point of this study was to observe the natural course of UTUC within 5 years between these two groups.…”
Section: Methodsmentioning
confidence: 99%
“…The follow-up protocol in the Taiwan and Japan cohorts is as disclosed in previous studies. 1,4 The endpoint of this study was to observe the natural course of UTUC within 5 years between these two groups. The oncologic outcomes we observed after nephroureterectomy were IVR, SR (including regional recurrence and distant metastasis defined by urothelial carcinoma recurrence outside the residual urinary tract) and cancer-specific death within 5 years.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We selected three courses of neoadjuvant GCb and this patient obtained the pathological complete response. Although inferior efficacy of a carboplatin‐based regimen has been suggested, our previous study showed a low toxicity GCb regimen facilitated in completion of NAC, prevention of the delay in RC, and resulted in a favorable oncological and QOL outcome . Therefore, neoadjuvant GCb might be an alternative option for MIBC patients with renal implement.…”
Section: Discussionmentioning
confidence: 94%